Link Between Cause of Paternal Death and Children’s Education Depends on Family Background - Sanna Kailaheimo; Sanni Kotimäki (Turku Center for Welfare Research/Turun yliopisto, 2022)
Early parental death has been linked to problems in children’s educational paths. We add to the literature by examining children’s education by cause of paternal death and family background. We compare whether a father’s death due to suicide, alcohol, accident or somatic causes is related to the children’s university education and examine these connections by childhood socioeconomic conditions.
Using Finnish register data and linear random-effects models, we analyse the university attendance of 108,875 children born between 1982–1992 by cause of paternal death and parental resources.
Results indicated lower education in bereaved children, especially in children who lost a highly educated father due to alcohol, suicide or accident. However, having a highly educated surviving mother related to a decrease in lower education in those children, suggesting maternal protection against adversities related to death. Causes of death and overall family circumstances should be considered when analysing child outcomes after parental death.